Diffuse ganglioneuromatosis of intestine in a 15-year-old girl. (22nd June 2011) - AHmad, Zubair; Khan, Rahil; Barakzai, Abrar; Ahmed, Arsalan; Qureshi, Asim
Abstract : The authors present the case of a 15-year-old girl with diffuse ganglioneuromatosis, principally involving the caecum. This is a rare condition and usually associated with multiple endocrine neoplasm IIb and neurofibromatosis type I. In our case, the myentric nerve plexus was exclusively involved. The patient presented with episodes of vomiting and weight loss. So far, to our knowledge no other manifestations of the above mentioned genetic conditions have become apparent in this patient.